Legal Responsibility of Notaries for Abuse of Circumstances in Making Deeds of Land Sale and Purchase Agreements - Alfarizyi, Dody; Meher, Montayana (CV. Publikasi Indonesia, 2025)
Notaries play a critical role in ensuring agreements are made freely and without coercion, yet cases arise where one party exploits another’s vulnerable economic, social, or psychological state, leading to unfair clauses. This article aims to analyze the legal responsibility of notaries for the abuse of circumstances in the making of land Sale and Purchase Binding Agreement (PPJB) deeds. The issue focuses on the role of the notary when one of the parties to the agreement is in a desperate or unbalanced condition, which has the potential to be exploited unfairly by the other party. To approach this problem, the theories of legal responsibility and defect of will are referenced. Data were collected through literature studies, laws and regulations, court decisions, and interviews with notaries, then analyzed qualitatively using a normative juridical approach. This study concludes that notaries are responsible not only administratively but also substantively in ensuring the free will of the parties. If proven negligent and there is an abuse of the situation, the notary can be held legally liable in civil terms or subject to ethical sanctions. Additionally, PPJB deeds made under unbalanced conditions can be annulled by the court on the basis of defect of will. This research emphasizes the importance of increasing notary sensitivity and professionalism to prevent abusive practices in the making of deeds.